Peningkatan Kemampuan Penalaran Matematika Siswa SMK Kelas X Melalui Pendekatan Realistic Mathematics Education (RME) - Erwin Triawan; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
This study aims to improve students' mathematical reasoning abilities through learning with the Realistic Mathematics Education approach. This research is a Classroom Action Research (CAR). The subject of the recipient of the action was 27th grade students of Industrial Chemistry at Jabir Al-Hayyan Vocational School. Methods of collecting data through observation, field notes, tests and documentation. The results showed an increase in students' mathematical reasoning. This can be seen from the increasing indicators of mathematical reasoning abilities including; 1) the ability to present mathematical statements in writing as much as 28.57% increased to (90%); 2) the ability to draw conclusions in response to existing problems by 38.10% increased to 70%; and 3) the ability to analyze mathematical situations using patterns and relationships as much as 23.81% increased to 65%. It can be concluded that the application of the Realistic Mathematics Education (RME) approach can improve students' mathematical reasoning abilities